2005
DOI: 10.1093/nar/gki822
|View full text |Cite
|
Sign up to set email alerts
|

RNase III cleavage demonstrates a long range RNA: RNA duplex element flanking the hepatitis C virus internal ribosome entry site

Abstract: Here, we show that Escherichia coli Ribonuclease III cleaves specifically the RNA genome of hepatitis C virus (HCV) within the first 570 nt with similar efficiency within two sequences which are ∼400 bases apart in the linear HCV map. Demonstrations include determination of the specificity of the cleavage sites at positions C27 and U33 in the first (5′) motif and G439 in the second (3′) motif, complete competition inhibition of 5′ and 3′ HCV RNA cleavages by added double-stranded RNA in a 1:6 to 1:8 weight rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(61 citation statements)
references
References 50 publications
2
58
0
Order By: Relevance
“…17 in Fig. 7, in 77 out of 77 isolates) has been described before in several studies (Honda et al 1999b;Wang et al 2000;Kim et al 2003;Beguiristain et al 2005). The interaction of 5 ′ UTR and Rep-Core is displayed in Supplemental Figure 2A.…”
Section: Long-range Interactionssupporting
confidence: 55%
“…17 in Fig. 7, in 77 out of 77 isolates) has been described before in several studies (Honda et al 1999b;Wang et al 2000;Kim et al 2003;Beguiristain et al 2005). The interaction of 5 ′ UTR and Rep-Core is displayed in Supplemental Figure 2A.…”
Section: Long-range Interactionssupporting
confidence: 55%
“…The RNA molecule representing the 59 end (59HCV-691) contained the first 691 nt of the HCV genome, therefore encompassing the whole 59 UTR and a significant portion of the core-coding sequence. This should resemble the functional folding of the IRES to be examined (Wang et al 2000;Kim et al 2003;Beguiristain et al 2005). For the 39 construct, the 39 UTR was extended at its 59 end with the three last hairpins of the NS5B coding sequence (39HCV-9181), thus enabling the correct interplay between these regions and favoring functional folding (You et al 2004;Friebe et al 2005).…”
Section: Resultsmentioning
confidence: 99%
“…The 59 core coding sequence shows a high sequence conservation rate, which was initially thought to be related to the existence of alternative reading frames (Walewski et al 2001;Xu et al 2001;Choi et al 2003;Branch et al 2005); however, its importance has recently been shown in the preservation of structures important for IRES activity and replication (domains V and VI) ( Fig. 1A; Wang et al 2000;Kim et al 2003;Beguiristain et al 2005;McMullan et al 2007;Vassilaki et al 2008). Within the 39 end of the NS5B coding sequence, the stem-loop 5BSL3.2 is embedded in a cruciform structure that has been identified as a cis-essential element for viral RNA synthesis (cis-acting replication element [CRE]) ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…These conformational changes involve the HCV IRES, which switches from a closed ‘circular’ conformation ‘C’ (5,7), formed by LRA (bases 24–38 in inter-domains I-II with bases 428–442 in the basal part of domain VI) to an open ‘O’ form (where bases 428–442 interact with bases 494–508; i.e. those forming the basal part of stem-loop VI).…”
Section: Discussionmentioning
confidence: 99%